2002
DOI: 10.1034/j.1600-0846.2002.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional analyses of individual corneocytes with atomic force microscope: morphological changes related to age, location and to the pathologic skin conditions

Abstract: To estimate the differentiation speed of the corneocytes, we suggest using their flatness index rather than the two-dimensional cell surface area, because the former is a concept that takes into account the three-dimensional characteristics of corneocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 18 publications
3
55
0
Order By: Relevance
“…21 While geometrical parameters change with age, structural entropy appears to be preserved during the maturation processes of infant epidermal structure. Since our focus has been so far on healthy skin, it is tempting to hypothesize that this parameter may be altered in certain disease cases, particularly in hyper-proliferative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…21 While geometrical parameters change with age, structural entropy appears to be preserved during the maturation processes of infant epidermal structure. Since our focus has been so far on healthy skin, it is tempting to hypothesize that this parameter may be altered in certain disease cases, particularly in hyper-proliferative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This has been traced back to differences in cell proliferation by Plewig [17], Kashibuchi et al [18] and Sakai et al [19]. In this study we also investigated two classes of subjects, i.e., healthy and diabetic subjects.…”
Section: Factors Influencing Mean Corneocyte Areamentioning
confidence: 99%
“…They observed a villous structure of cells from thick skin with their surface pointing towards the dermis, but did not study the counterpart surface. Here, by means of a simple procedure using a conductive adhesive tape, SEM measurements of the dehydrated corneocytes surface, towards the in-and outside of the body, were carried out successfully for thick and thin skin samples, showing significant morphological differences in their ultra-structures [17][18][19][20][21][22][23]. Ex vivo corneocyte structures were investigated in order to better understand also the mechanisms that regulate desquamation at the epidermal surface, as well as mechanical stability of the stratum corneum as studied shortly before by Wu et al [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the typical thickness of corneocytes (around 200-500 nm), investigation at the level of single corneocytes by optical microscopy is rather difficult, especially if changes in thickness need to be measured. Atomic force microscopy, on the other hand, has the resolution power but enables only investigation of single cell, which swell about 50% in thickness [8,9], but never the complete SC. Since both methods have shown that corneocytes and the entire SC preferentially swell only vertically, the question arose whether the skin barrier remains stable with such massive volume changes, especially as Warner et al [10] had shown that extended water exposure disrupts the SC ( fig.…”
Section: Introductionmentioning
confidence: 99%